Using Options Futures Derivatives Weather in Hedging - Faez Hasan, Mohammed; Al-Ramadan, Noor Salah Abdelnaby (Technium Social Sciences Journal, 2022)
The present investigation is taken into consideration on using options futures derivatives weather in hedging. A weather derivative is considered as the financial instrument that people or firms use to protect themselves from the threat of weather-related losses. In exchange for a premium, the seller of a weather variant concurs to assume the risk of disasters. Weather hedges are regarded as the financial instrument used by businesses or individuals to limit the risk of weather loss. There have been different articles considered based on the given subject area. The findings stated that heating degree days is one climate index for weather derivatives. Each day that the daily average temperature tends to fall under a predefined reference point over a specified time, the deviation amount is recorded as well as decided to add to an accumulated count under HDD agreements. From the above-mentioned information, it has been concluded that there are numerous obstacles to making effective use of and managing weather options. Risk managers should understand options, as well as the risk profile related to the purchase of weather options about their company, can find weather derivatives extremely useful. Adding weather possibilities to the Value at Risk (VAR) calculation is a simple process.